Impact of Specialized Pro-Resolving Lipid Mediators on Craniofacial and Alveolar Bone Regeneration: Scoping Review - Rovai, Emanuel da Silva [UNESP]; Polassi, Mackeler; da Silveira, Marcela Iunes [UNESP]; Araújo, Sandy Lima; Van Dyke, Thomas; Dos Santos, Nidia C. Castro (FapUNIFESP (SciELO), 2024)
Craniofacial bone defects caused by tumors, trauma, long-term tooth loss, or periodontal disease are a major challenge in the field of tissue engineering. In periodontitis and peri-implantitis, reconstructive therapy is also a major challenge for the dental surgeon. Lipoxins, resolvins, protectins, and maresins, known as specialized pro-resolving lipid mediators (SPMs), have been widely studied in the field of dental, oral, and craniofacial research for bone regeneration for their actions in restoring tissue homeostasis and promoting tissue healing and regeneration. Therefore, this study focuses on a survey of the use of SPMs for craniofacial and alveolar bone regeneration. Thus, electronic searches of five databases were performed to identify pre-clinical studies that evaluated the actions of SMPs on craniofacial and alveolar bone regeneration. Of the 523 articles retrieved from the electronic databases, 19 were included in the analysis. Resolvin (Rv) E1 was the mostly assessed SPM (n=8), followed by maresins (Ma) R1 (n=3), lipoxins (Lx) A4 (n=3), RvD1 (n=3), RvD2 (n=1), LxB4 (n=1), and maresin (M)-CTR3 (n=1). Meta-analysis showed that SPMs increased the newly formed bone by 14.85% compared to the control group (p<0.00001), decreased the area of the remaining defect by 0.35 mm2 (p<0.00001), and decreased the linear distance between the defect to the bone crest by 0.53 mm (p<0.00001). RvE1 reduced inflammatory bone resorption in periodontal defects and calvarial osteolysis and enhanced bone regeneration when RvE1 was combined with a bovine bone graft. RvD2 induced active resolution of inflammation and tissue regeneration in periapical lesions, while RvD1 controlled the inflammatory microenvironment in calvarial defects in rats, promoting bone healing and angiogenesis. MaR1 induced the proliferation and migration of mesenchymal stem cells, osteogenesis, and angiogenesis in calvarial defects, and benzo (b)-LxA4 and LxA4 promoted bone regeneration calvarial and alveolar bone defects in rats, inducing regeneration under inflammatory conditions. In summary, SPMs have emerged as pivotal contributors to the resolution of inflammation and the facilitation of bone neoformation within craniofacial and alveolar bone defects. These results are based on pre-clinical studies, in vivo and in vitro, and provide an updated review regarding the impact of SPMs in tissue engineering.
Keywords: Bone regeneration; lipoxins; maresins; resolvins; specialized pro-resolving lipid mediators